Scrolling into Vocabulary: The Process, Challenges, and Outcomes of Learning English Through Digital Authentic Materials Among Indonesian Senior High School Students - Yanti Suryanti; R. Lungguh Halira Vonti; Ummul Badriah Atikoh (UNIVERSITAS PAKUAN, 2026)
Vocabulary is a foundational component of second-language acquisition, yet the rich Digital Authentic Materials (DAM) that senior high school students consume daily remain pedagogically underused. This study investigated the process, challenges, and outcomes of English vocabulary learning through DAM—YouTube, podcasts, and social media—among students of SMA Negeri 3 Bogor, Indonesia. Adopting a qualitative instrumental case-study design with an embedded quantitative component, data were gathered from 28 tenth-grade students through a structured questionnaire combining Likert scales and open-ended items, and from an in-depth interview with an English teacher serving as a supporting informant. Quantitative data were analyzed descriptively (means, standard deviations, internal-consistency reliability), while qualitative data were analyzed thematically following Braun and Clarke. Findings show that YouTube and TikTok were the dominant platforms and that students engaged actively with DAM (composite M = 3.95), most often inferring meaning from multimodal context or consulting online dictionaries. Students perceived DAM as markedly different from textbooks (M = 4.14), valuing its engaging and audio visual nature. The most frequently reported challenges were rapid speech and unfamiliar slang, while affective and access barriers were comparatively minor. Reported vocabulary growth (M = 3.59) and confidence gains (M = 3.68) were moderately positive, with slang and informal conversational vocabulary acquired most. The teacher corroborated the contextual richness of authentic materials while emphasizing difficulty calibration and the need for digital infrastructure and training. The study contributes context-specific evidence for DAM-based vocabulary pedagogy and offers practical guidance for teachers, schools, and teacher-education programs in the Indonesian context.